Hegemony of Independent Campus Learning (Antonio Gramsci's Hegemony Study in the Indonesia Education System) - Robin, Patricia; Ronda, Andi Mirza; Napitupulu, Frengki (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Freire once revealed how education could liberate with the essence of